Method for preparing fine-grained ammonium heptamolybdate by aid of crystallization process
By using additive crystallization and vacuum evaporation, the problems of large and uneven particle size in the preparation of ammonium heptamolybdate were solved, and high-purity, narrow-size fine-grained ammonium heptamolybdate crystals were prepared, meeting the needs of high-end applications and reducing production costs.
Patent Information
- Application Number
- CN202511520966.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-01-13
AI Technical Summary
Existing technologies for preparing ammonium heptamolybdate suffer from large and uneven particle size, low solution supersaturation and uneven crystal growth rate due to traditional crystallization processes, and high production costs, making it difficult to meet the needs of high-end applications.
Fine-grained ammonium heptamolybdate crystals were prepared by using an auxiliary crystallization method and a vacuum evaporation method, which promoted the conversion of molybdate ions to high polymerization degree by using crystallization aids and ultrasonic-assisted treatment, thus simplifying the production process and avoiding high-temperature environments.
The preparation of high-purity, narrow-size fine-grained ammonium heptamolybdate crystals has been achieved, which improves dispersibility and processing performance, reduces production costs, and meets the needs of high-end applications.
Smart Images

Figure CN121317875A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of ammonium heptamolybdate preparation, and relates to ammonium heptamolybdate, in particular to a method for preparing fine-grained ammonium heptamolybdate crystals by an additive crystallization method. BACKGROUND
[0002] Ammonium heptamolybdate is an important molybdenum compound, which can be used to prepare molybdenum metal powder, molybdenum ceramics (such as MoSi2) and electronic packaging materials; however, the particle size characteristics of ammonium heptamolybdate have a profound impact on its application, because coarse particles in the traditional method can easily lead to poor sintered body density or unstable electrical properties, while ultra-fine particles (1-5 μm) can reduce the sintering temperature (from 1600 ℃ to 1400 ℃), improve the ceramic density and the uniformity of electrical conductivity, and meet the demand for high-performance materials in 5G communication and semiconductor packaging. In addition, ammonium heptamolybdate also has great application value as a catalyst precursor, for example: ammonium heptamolybdate can be used as a precursor to prepare petroleum hydrodesulfurization (HDS) catalysts and olefin polymerization catalysts. However, the current preparation of these catalysts generally uses large-particle ammonium molybdate (>50 μm), but the poor dispersibility of large-particle active components leads to low catalytic efficiency; therefore, as a catalyst precursor, ammonium heptamolybdate is generally required to have a small crystal particle size. However, the industrial ammonium heptamolybdate currently produced on the market has a relatively large particle size, thus limiting the application range of ammonium heptamolybdate; in addition, the low stirring efficiency in the traditional crystallization kettle (such as paddle stirring) or the residual mother liquor on the surface of the particles when the wet material is slowly dehydrated can easily form "liquid bridges", which can cause ammonium heptamolybdate to easily form lumps and also cause the ammonium heptamolybdate crystal grains to become large, and the poor flowability of large particles can result in poor dispersibility in subsequent processing (such as catalyst carrier loading), thus reducing the performance of the product.
[0003] Whether it is from catalysts to new energy, fine-grained ammonium heptamolybdate crystals can meet the demand for material performance in high-end applications and green manufacturing by improving dispersibility, activity and processing performance. The particle size control of ammonium heptamolybdate will become a key indicator of the competitiveness of the molybdenum chemical industry and a core technology development direction.
[0004] The current industrial method for preparing ammonium heptamolybdate is: using ammonium tetramolybdate or ammonium dimolybdate as raw material, dissolving the ammonium molybdate, and then adjusting the pH by adding nitric acid or sulfuric acid, supplemented by temperature control, to make the ammonium molybdate undergo structural rearrangement and convert the ammonium molybdate into ammonium heptamolybdate. The working mechanism of this method is to adjust the solution properties (pH, temperature) to control the polymerization degree of molybdate in the solution: to make the low-polymerization-degree ammonium tetramolybdate chemically convert into high-polymerization-degree ammonium heptamolybdate. Although the existing method can prepare ammonium heptamolybdate, it still has the following problems: (1) The traditional crystallization process usually adopts slow cooling or natural evaporation, resulting in low supersaturation of the solution and slow release; at this time, the crystal growth rate (controlled by diffusion) is much higher than the nucleation rate, so the final ammonium heptamolybdate product still has large grains; in addition, if the stirring rate is low during the crystallization process, the crystal nuclei cannot be dispersed in time, resulting in too high local supersaturation, which causes explosive nucleation and abnormal growth, and finally forms crystals with uneven size; (2) Currently, ammonium heptamolybdate is produced by using ammonium tetramolybdate or ammonium dimolybdate; however, the production of ammonium tetramolybdate consumes a large amount of nitric acid, and ammonium nitrate produced in the acid precipitation process is a regulated chemical, which leads to high production cost of ammonium heptamolybdate; ammonium dimolybdate requires very precise regulation (pH, temperature) of the ammonium molybdate solution to be prepared; if the pH is too low (<5.0), heteropoly molybdates (such as phosphomolybdate, silicon molybdate) may be generated in the solution, reducing the purity of ammonium heptamolybdate; if the pH is too high (>5.5), ammonium tetramolybdate cannot be fully converted into ammonium heptamolybdate, and residual ammonium tetramolybdate in the product also reduces the product purity. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application proposes a method for preparing fine-grained ammonium heptamolybdate crystals by an additive crystallization method to solve the technical problems of large particle size and uneven crystal size in the preparation of ammonium heptamolybdate in the prior art.
[0006] To solve the above technical problems, the present application adopts the following technical solutions: A method for preparing fine-grained ammonium heptamolybdate crystals by an additive crystallization method, characterized in that the method specifically comprises the following steps: Step one, preparation of ammonium molybdate solution: Step 1.1, weigh concentrated ammonia and dissolve it in deionized water to obtain an ammonia solution; Step 1.2, weigh molybdenum oxide and dissolve it in the ammonia solution obtained in step 1.1, stir uniformly, and then cool to room temperature to obtain an ammonium molybdate solution, and measure the pH value of the ammonium molybdate solution; Step two, additive crystallization of ammonium molybdate solution: At room temperature, take the ammonium molybdate solution of step one into a beaker, and under stirring conditions, add a crystallization aid to the ammonium molybdate solution to make the ammonium molybdate solution precipitate crystals; stir until the crystallization is complete, and then separate the ammonium heptamolybdate filter cake by standing, filtering and separating; and wash the ammonium heptamolybdate filter cake with an ethanol aqueous solution; Step three, preparation of fine-grained ammonium heptamolybdate crystals by evaporation under reduced pressure: Step 3.1, dissolve the ammonium heptamolybdate filter cake obtained in step two in deionized water, and stir thoroughly until an ammonium heptamolybdate solution is formed; Step 3.2, the ammonium heptamolybdate solution in step 3.1 is measured in an evaporator, and then a crystallization aid is added and subjected to reduced pressure evaporation, and after the reduced pressure evaporation is completed, drying is performed to obtain fine-grained ammonium heptamolybdate crystals.
[0007] The present application also has the following technical features: Preferably, in step 1.1, the mass fraction of the concentrated ammonia water is 25% to 28%.
[0008] Preferably, in step 1.2, the molybdenum oxide is obtained by roasting molybdenum concentrate, and the pH value of the ammonium molybdate solution is 9.42.
[0009] Preferably, in step 2, the volume ratio of the crystallization aid to the ammonium molybdate solution is (1.0 to 3.0):1.
[0010] Preferably, in step 2, the aqueous ethanol solution is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1.
[0011] Preferably, in step 3.1, the ammonium heptamolybdate solution is a saturated ammonium molybdate solution or an unsaturated ammonium molybdate solution.
[0012] Preferably, in step 3.2, the volume ratio of the ammonium heptamolybdate solution to the crystallization aid is (5 to 8):1.
[0013] Preferably, in step 3.2, ultrasonic assistance is used during the reduced pressure evaporation process, the frequency of the ultrasonic assistance is 20 to 40 kHz, and the time of the ultrasonic assistance is not less than 20 minutes.
[0014] Preferably, the crystallization aid is methanol, ethanol, isopropyl alcohol, isobutyl alcohol, isoamyl alcohol, isopentyl alcohol, isopentyl glycol, acetone, butanone, tetrahydrofuran, N,N-dimethylformamide, acetonitrile, petroleum ether, triethanolamine, inositol, or phytic acid.
[0015] Preferably, in step 3, the temperature of the reduced pressure evaporation is not less than 30°C, and the pressure of the reduced pressure evaporation is not higher than 0.08 MPa.
[0016] Compared with the prior art, the present application has the following beneficial technical effects: (I) In the present application, molybdenum oxide is used as the raw material, and the synergistic effect of the crystallization aid and the reduced pressure evaporation is used to form ammonium heptamolybdate. The reduced pressure evaporation increases the molybdenum concentration in the solution, thereby inducing the conversion of molybdate ions to a high degree of polymerization, significantly promoting the formation of ammonium heptamolybdate. The crystallization aid can promote the formation of crystals and refine the ammonium heptamolybdate crystal particles, thereby obtaining fine-grained ammonium heptamolybdate crystal products with high purity and narrow particle size distribution.
[0017] (II) In the present application, ultrasonic assistance is used during the reduced pressure evaporation process, which can further reduce crystal agglomeration and improve the dispersibility of the crystals.
[0018] (III) The application uses an auxiliary agent crystallization method to prepare ammonium heptamolybdate from molybdenum oxide as a raw material in one step, without generating ammonium molybdate intermediates such as ammonium tetramolybdate and ammonium dimolybdate, saving the intermediate product step, simplifying the production method process of ammonium heptamolybdate, and improving the production efficiency.
[0019] (IV) The application directly realizes the preparation of fine-grained ammonium heptamolybdate crystals by using auxiliary agent crystallization and reduced pressure evaporation, without precise control of the pH of the ammonium molybdate solution; at the same time, the auxiliary agent crystallization method has a fast crystallization speed, a short cycle, and does not require a high-temperature environment, and is safe and reliable. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 Figure 1 is an X-ray diffraction characterization diagram of a standard ammonium heptamolybdate sample.
[0021] Figure 2(a) is an electron scanning microscope characterization diagram of the fine-grained ammonium heptamolybdate crystal product prepared in Example 1.
[0022] Figure 2(b) is an electron scanning microscope characterization diagram of the fine-grained ammonium heptamolybdate crystal product prepared in Example 2.
[0023] Figure 3(a) is a Mo content analysis diagram of the fine-grained ammonium heptamolybdate crystal product prepared in Example 1.
[0024] Figure 3(b) is a Mo content analysis diagram of the fine-grained ammonium heptamolybdate crystal product prepared in Example 2.
[0025] The specific content of the application will be further explained and described in detail in combination with the following examples. DETAILED DESCRIPTION
[0026] It should be noted that all the equipment and materials in the application, if not specifically stated, all use the equipment and materials known in the prior art.
[0027] In accordance with the above technical solution, the following specific examples of the application are given. It should be noted that the application is not limited to the following specific examples, and any equivalent transformation based on the technical solution of the present application falls within the scope of protection of the present application.
[0028] Example 1: The present embodiment gives a method for preparing fine-grained ammonium heptamolybdate crystals by an auxiliary agent crystallization method, which specifically includes the following steps: Step one, preparation of an ammonium molybdate solution by an ammonia immersion method: Step 1.1, weigh 40 mL of concentrated ammonia water with a mass fraction of 25% to 28% and dissolve it in 40 mL of deionized water to obtain an ammonia water solution; Step 1.2, 20 g of molybdenum oxide was weighed and dissolved in the ammonia solution in step 1.1, and after stirring uniformly and cooling to room temperature, an ammonium molybdate solution was obtained, and the pH value of the ammonium molybdate solution was measured to be 9.42; In this embodiment, the molybdenum oxide is obtained by roasting molybdenum concentrate, and the roasting method is the existing conventional method. The roasting process mainly breaks and grinds the molybdenum concentrate (main component is molybdenum disulfide MoS2) into fine powder (particle size is usually less than 0.074 mm) to increase the reaction contact area and improve the roasting efficiency, and then in a high-temperature oxidation atmosphere, the molybdenum concentrate (MoS2) reacts with oxygen to generate molybdenum oxide (MoO3).
[0029] Step two, ammonium molybdate solution additive crystallization: At room temperature, 100 mL of the ammonium molybdate solution in step one was taken in a 1 L beaker, and 100 mL of tetrahydrofuran was added to the ammonium molybdate solution under stirring conditions to make the ammonium molybdate solution precipitate crystals, and the stirring was continued for 20 min until the crystallization was complete, and then the solution was allowed to stand for 10 min, filtered and separated to obtain an ammonium heptamolybdate filter cake, which was washed with an ethanol aqueous solution. In this embodiment, the system after crystallization is separated without drying, so that the ammonium heptamolybdate filter cake obtained does not contain other ammonium molybdate intermediates (ammonium tetramolybdate and ammonium dimolybdate), which not only simplifies the preparation process, but also helps to prepare fine-grained ammonium heptamolybdate crystals.
[0030] In this embodiment, anhydrous ethanol and water (deionized water) are mixed in a volume ratio of 1:1 to form an ethanol aqueous solution. The washing is carried out by mixing the ammonium heptamolybdate filter cake and the ethanol aqueous solution and then placing them in a centrifuge for washing. The washing conditions are as follows: the ethanol aqueous solution should be as much as possible to submerge the filter cake, the centrifuge speed is set to 10000 r / min, and the washing time is 90 seconds.
[0031] Step three, preparation of fine-grained ammonium heptamolybdate crystals by evaporation under reduced pressure: Step 3.1, the ammonium heptamolybdate filter cake obtained in step two was dissolved in deionized water, and stirred thoroughly until an ammonium heptamolybdate solution was formed; In this embodiment, the ammonium heptamolybdate solution is a saturated ammonium heptamolybdate solution or an unsaturated ammonium heptamolybdate solution.
[0032] Step 3.2, 10 mL of the ammonium molybdate solution in step 3.1 was taken in an evaporator, and then 2 mL of N,N-dimethylformamide was added for evaporation under reduced pressure, the evaporation temperature was set to 70°C, the pressure for evaporation under reduced pressure was 0.08 MPa, and after the evaporation under reduced pressure was completed, drying was carried out to obtain fine-grained ammonium heptamolybdate crystals.
[0033] In this embodiment, after the evaporation under reduced pressure is completed, the obtained ammonium heptamolybdate crystals are placed in an oven at 40°C until they are thoroughly dried to obtain fine-grained ammonium heptamolybdate crystals.
[0034] Example 2 In this example, a method for preparing fine-grained ammonium heptamolybdate crystals by using an auxiliary crystallization method is provided. The steps of this method are basically the same as those of Example 1, with the only difference being that: In Step 3.2, ultrasonic assistance is used during the process of reduced pressure evaporation. The frequency of ultrasonic assistance is 30 kHz, and the time of ultrasonic assistance is 30 min.
[0035] In this example, ultrasonic assistance optimizes the crystallization process of ammonium heptamolybdate through physical effects (cavitation, vibration, and microjet). The core goal is to obtain fine-grained products with small particle size, narrow distribution, and regular morphology, while improving the efficiency of the method. The use of ultrasonic assistance can reduce crystal agglomeration and improve crystal dispersibility.
[0036] In this example, XRD (X-ray diffraction) tests are performed on standard ammonium heptamolybdate crystals, fine-grained ammonium heptamolybdate crystals prepared in Example 1, and fine-grained ammonium heptamolybdate crystals prepared in Example 2. The results are shown in Figure 2. According to the analysis of the XRD results in Figure 2, the XRD characteristic peaks of the sample in Example 1 (fine-grained ammonium heptamolybdate crystals) are consistent with those of standard ammonium heptamolybdate crystals. The crystalline product is fine-grained ammonium heptamolybdate crystals. The XRD characteristic peaks of the sample in Example 2 (fine-grained ammonium heptamolybdate crystals) are consistent with those of standard ammonium heptamolybdate crystals. The crystalline product is fine-grained ammonium heptamolybdate crystals, indicating that fine-grained ammonium heptamolybdate crystals are successfully prepared in this example. Figure 1
[0037] In this example, SEM (scanning electron microscope) tests are performed on fine-grained ammonium heptamolybdate crystals prepared in Example 1 and fine-grained ammonium heptamolybdate crystals prepared in Example 2. The results are shown in Figure 2 (a) and Figure 2 (b). Figure 2 (a) is a scanning electron microscope image of fine-grained ammonium heptamolybdate crystals prepared in Example 1, and Figure 2 (b) is a scanning electron microscope image of fine-grained ammonium heptamolybdate crystals prepared in Example 2. As can be seen from Figure 2 (a) and Figure 2 (b), the average particle size of fine-grained ammonium heptamolybdate crystals prepared in Example 1 and Example 2 is less than 100 μm, indicating that fine-grained ammonium heptamolybdate crystals are prepared by auxiliary crystallization and reduced pressure evaporation in this example. In addition, it is found that the ammonium heptamolybdate crystals obtained in Example 2 are smaller than those obtained in Example 1, indicating that the use of ultrasonic assistance in reduced pressure evaporation helps to obtain ammonium heptamolybdate crystals with smaller particle size.
[0038] In the embodiment, the fine particle grade ammonium heptamolybdate crystals prepared in Example 1 and the fine particle grade ammonium heptamolybdate crystals prepared in Example 2 are respectively subjected to ICP (inductively coupled plasma) test, and the results are shown in Figure 3(a) and Figure 3(b). Figure 3(a) is a Mo element standard curve obtained in the ICP test of the fine particle grade ammonium heptamolybdate crystals prepared in Example 1, and Figure 3(b) is a Mo element standard curve obtained in the ICP test of the fine particle grade ammonium heptamolybdate prepared in Example 2.
[0039] In the embodiment, Table 1 is a Mo element spectrum intensity and element concentration control table, Table 2 is the Mo element ICP test result of the fine particle grade ammonium heptamolybdate crystals in Example 1, and Table 3 is the Mo element ICP test result of the fine particle grade ammonium heptamolybdate crystals in Example 2.
[0040] Table 1 Mo element spectrum intensity and element concentration control table
[0041] Table 2 Mo element test result in the sample of Example 1
[0042] Table 3 Mo element test result in the sample of Example 2
[0043] From Table 1 and Table 2, it can be calculated that the Mo content of the fine particle grade ammonium heptamolybdate crystals prepared in Example 1 is 55.01%, which is close to the Mo content of standard ammonium heptamolybdate hydrate. As can be seen from the concentration point line graph of the sample of Example 1 and the standard ammonium heptamolybdate solution in Figure 3(a), the Mo content of the fine particle grade ammonium heptamolybdate sample prepared in Example 1 meets the standard, and the Mo content of the sample is well consistent with that of the standard ammonium heptamolybdate sample.
[0044] From Table 1 and Table 3, it can be calculated that the Mo content of the fine particle grade ammonium heptamolybdate crystals prepared in Example 2 is 54.61%, which is close to the Mo content of standard ammonium heptamolybdate hydrate. As can be seen from the concentration point line graph of the sample of Example 1 and the standard ammonium heptamolybdate solution in Figure 3(b), the Mo content of the fine particle grade ammonium heptamolybdate sample prepared in Example 2 meets the standard, and the Mo content of the sample is well consistent with that of the standard ammonium heptamolybdate sample.
[0045] The above performance tests are carried out on the fine particle grade ammonium heptamolybdate crystals prepared in Example 1 and Example 2. When the type of crystallization aid, the volume of crystallization aid, and the parameters of vacuum evaporation are selected and replaced, the fine particle grade ammonium heptamolybdate crystals prepared have the same or similar performance as those of Example 1 or Example 2. The present application prepares fine particle grade ammonium heptamolybdate with high purity and narrow particle size distribution through aid crystallization and vacuum evaporation, which is convenient for application in industry.
Claims
1. A method for preparing fine-grained ammonium heptamolybdate crystals by an auxiliary crystallization method, the method specifically comprising the following steps: Step 1: Prepare ammonium molybdate solution: Step 1.1: Weigh concentrated ammonia water and dissolve it in deionized water to obtain an ammonia solution; Step 1.2: Weigh molybdenum oxide and dissolve it in the ammonia solution from Step 1.
1. Stir well and cool to room temperature to obtain ammonium molybdate solution. Measure the pH value of the ammonium molybdate solution. Its features are: Step 2, crystallization of ammonium molybdate solution as an auxiliary agent: At room temperature, measure the ammonium molybdate solution from step one into a beaker. Under stirring, add a crystallization aid to the ammonium molybdate solution to precipitate crystals. Stir until crystallization is complete, let stand, filter, and separate to obtain an ammonium heptamolybdate filter cake. Wash the ammonium heptamolybdate filter cake with an ethanol aqueous solution. Step 3: Prepare fine-grained ammonium heptamolybdate crystals by vacuum evaporation: Step 3.1: Dissolve the ammonium heptamolybdate filter cake obtained in step 2 in deionized water and stir thoroughly until an ammonium heptamolybdate solution is formed; Step 3.2: Measure the ammonium heptamolybdate solution from step 3.1 into an evaporator, add a crystallization aid, and then evaporate under reduced pressure. After the reduced pressure evaporation is completed, dry the solution to obtain fine-grained ammonium heptamolybdate crystals.
2. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 1, characterized in that, In step 1.1, the mass fraction of concentrated ammonia solution is 25%–28%. In step 1.2, molybdenum oxide is obtained by roasting molybdenum concentrate, and the pH value of the ammonium molybdate solution is 9.
42.
3. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 1, characterized in that, In step two, the volume ratio of the crystallization aid to the ammonium molybdate solution is (1.0 to 3.0):
1. In step two, the ethanol-water solution is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:
1.
4. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 1, characterized in that, In step 3.1, the ammonium heptamolybdate solution is either a saturated ammonium heptamolybdate solution or an unsaturated ammonium heptamolybdate solution; In step 3.2, the volume ratio of ammonium heptamolybdate solution to crystallization aid is (5-8):
1.
5. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 4, characterized in that, In step 3.2, ultrasonic-assisted treatment is performed during the reduced pressure evaporation process. The frequency of ultrasonic assistance is 20-40 kHz, and the duration of ultrasonic assistance is not less than 20 min.
6. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 1, characterized in that, Crystallization aids include methanol, ethanol, isopropanol, isobutanol, isoamyl alcohol, isopentyl alcohol, isopentyl glycol, acetone, butanone, tetrahydrofuran, N,N-dimethylformamide, acetonitrile, petroleum ether, triethanolamine, inositol, or phytic acid.
7. The method for preparing fine-grained ammonium heptamolybdate crystals by the auxiliary crystallization method as described in claim 1, characterized in that, In step three, the temperature of vacuum evaporation shall not be lower than 30℃, and the pressure of vacuum evaporation shall not be higher than 0.08MPa.